Preferential weld corrosion of carbon steels - McIntyre, Dale; Achour, Mohsen (NACE International, 2016)
This book addresses the detection, assessment and control of preferential weld corrosion (PWC) of carbon steels. Corrosion professionals, asset integrity specialists and engineers responsible for risk management will find a comprehensive literature survey, detailed description of the PWC problem in its different aspects, and clear guidance on how to manage PWC in both new projects and maturing assets. Detailed case histories describe PWC and its mitigation in seawater pipelines, cooling water systems, wet gas piping, heat exchangers and related process equipment. And monographs published during the past 60 years or so are cited in the text. This book not only provides technical information about internal corrosion control, but also provides suggestions and potential strategies for applying this information. The fundamental process of managing internal corrosion consists of threat assessment, mitigation selection and implementation, and monitoring the effectiveness of mitigation.
Keywords: Welding.; Welded joints -- Quality control.; Welded joints -- Testing.; elektronické knihy; electronic books